Kincir Air Bambu Ikon Kampung Wisata Edukatif Desa Ciburial - Mulyawati, Fauzia; Husniah, Hennie; Sujana, Rd. Octavia Maryanche; Suhendra, Eddy (Jurnal Pengabdian Tri Bhakti, 2020)
Development does not always have a positive impact on the life of an area. The level of development in general is always inversely proportional to sustainability. As evidence of the reduction in open green land because there have been many increases in the number of shopping centers, and hotels which are one of the means of city tourism. Or, long and sustainable impacts such as climate change and air temperatures and the depletion of groundwater supplies which results from the increasing number of residential developments that are part of the economic development of the people of Bandung. North Bandung area which is essentially a water catchment area and conservation area in the city of Bandung was not separated from the impact of the development. The construction of luxury residences, public facilities such as hotels and restaurants and other artificial natural attractions have been built on open green land, conservation areas and water catchment areas. At Kampung Lebaksiuh, Desa Ciburial, Sub-district Cimenyan, Kabupaten Bandung which is in the northern Bandung region, is one of the few indigenous settlements that still maintain the function of conservation and water catchment areas. With the various problems above, this community service activity aims to make a waterwheel as one of the educational tools for visitors, especially children who come to visit the Lebaksiuh Tourism Village, Desa Ciburial, Sub-district Cimenyan, Kabupaten Bandung.